Cluster Analysis Using K-Means Method to Classify Sumatera Regency and City Based on Human Development Index Indicator - Muhammad Faishal Jundana Muttaqin (Seminar Nasional Official Statistics, 2022)
Human development progress in Indonesia is characterized by the increasing score of Human Development Index (HDI). HDI is an important indicator in measuring efforts to build the quality and equity of human life. HDI consists of four variables including life expectancy at birth, school continuity, average of school continuity and expenditure per capita. In this study, we classify districts or cities on the island of Sumatra based on HDI into three categories; high, middle, and low area. We use cluster analysis for the research. Cluster analysis is a class of multivariate techniques that are used to classify objects or cases into relative groups called clusters. One of the cluster analysis methods is k-means. The result of this research divided into three Cluster. The first cluster or the middle area contained 41 cities. The second cluster or the high area contained 21 regencies/cities. The third cluster or the low area contained 92 regencies /cities. Areas with low scores are of more concern because all indicators are below the average value, these areas are like Pidie, Nias Utara, Pesisir Barat and etc.